2019
DOI: 10.1007/s12192-018-0934-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of a serine protease gene (AccSp1) from Apis cerana cerana in abiotic stress responses and innate immunity

Abstract: Clip-domain serine proteases (Clip-SPs) mediate innate immunity and embryonic development in insects. However, the function of Clip-SPs in Apis cerana cerana is little known. Here, a Clip-SP gene, AccSp1, was identified. AccSp1 was mainly detected in third and sixth day instar larvae, dark-eyed pupae, and adults (1and 30 days post-emergence). In addition, AccSp1 was expressed at its highest level in the venom gland and epidermis than tentacle, abdomen, muscle, honey sac, head, leg, chest, hemolymph, rectum, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Although many CLIPs have been identified and characterized in insects, the functions of most CLIPs are unknown (Kanost and Jiang, 2015). In Apis cerana cerana, a CLIP gene (AccSP1) is found to play crucial roles in the defense of abiotic stresses and resistance to pathogens (Gao et al, 2019). In B. mori, only three CLIP genes (CLIP1, CLIP2, and SP95) are documented to be involved in innate immune and integument remodeling during molting (Zhao et al, 2010;Liu et al, 2017).…”
Section: Function Of Lsclip3 Involved In Innate Immunitymentioning
confidence: 99%
“…Although many CLIPs have been identified and characterized in insects, the functions of most CLIPs are unknown (Kanost and Jiang, 2015). In Apis cerana cerana, a CLIP gene (AccSP1) is found to play crucial roles in the defense of abiotic stresses and resistance to pathogens (Gao et al, 2019). In B. mori, only three CLIP genes (CLIP1, CLIP2, and SP95) are documented to be involved in innate immune and integument remodeling during molting (Zhao et al, 2010;Liu et al, 2017).…”
Section: Function Of Lsclip3 Involved In Innate Immunitymentioning
confidence: 99%
“…Studies have shown that B. bombysepticus infection in silkworms leads to the upregulation of serine protease inhibitor genes ( 4 ). Additionally, B. bombysepticus has also been shown to be lethal to bees ( 5 ); however, little is known about its pathogenicity in humans.…”
Section: Announcementmentioning
confidence: 99%